PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI CV. PROZIGI GRAPHIC, KABUPATEN TANGERANG - Devi Irawati; Ambar Widya Lestari (Journal of Research and Publication Innovation, 2025)
This research aims to find out how leadership style and work environment influence the performance of CV employees. Prozigi Graphic Tangerang Regency. This research method uses quantitative descriptive methods. Data collection techniques were carried out through questionnaires processed using SPSS version 26.0. The population used in this research was 62 employees. The sampling technique used saturated sampling and a sample of 62 respondents was obtained. The data analysis techniques used are descriptive analysis, data instrument testing, classical assumption testing, correlation coefficient analysis, coefficient of determination analysis, quantitative testing, and hypothesis testing (t and f tests). The research results show that leadership style partially has a significant effect on employee performance with the regression equation Y = 6.359 + 0.914 X1 and a correlation coefficient value of 0.821. The work environment also has a partially significant effect with the regression equation Y = 13.207 + 0.695 X2 and a correlation coefficient of 0.668. The F test shows Fcount > Ftable, namely F 67.493 > 2.371 which confirms that leadership style and work environment simultaneously influence employee performance.